2015
DOI: 10.1016/j.pss.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Testing the ability of the ExoMars 2018 payload to document geological context and potential habitability on Mars

Abstract: a b s t r a c tThe future ExoMars rover mission (ESA/Roscosmos), to be launched in 2018, will investigate the habitability of the Martian surface and near subsurface, and search for traces of past life in the form of textural biosignatures and organic molecules. In support of this mission, a selection of relevant Mars analogue materials has been characterised and stored in the International Space Analogue Rockstore (ISAR), hosted in Orléans, France. Two ISAR samples were analysed by prototypes of the ExoMars r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…ExoMars program). Indeed, in the last years, Raman spectroscopy has been recognized as a promising tool for in situ and/or remote investigation of organic and inorganic material of bodies in our solar system . In particular, it has been demonstrated that Raman spectroscopy can be used both in situ and in remote conditions up to 100 m [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ExoMars program). Indeed, in the last years, Raman spectroscopy has been recognized as a promising tool for in situ and/or remote investigation of organic and inorganic material of bodies in our solar system . In particular, it has been demonstrated that Raman spectroscopy can be used both in situ and in remote conditions up to 100 m [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Named 00 AU05 in the ISAR collection, sample A (Figure a) had a fine‐grained appearance and was characterized by light‐ and dark‐colored layers. Visual observation and thin section analysis showed that the differences in color between the black and white layers are related to grain size, the darker layers being finer grained than the white ones [ Bost et al ., ]. The outcrop from which the sample originated, 3.446 Gy‐old Kitty's Gap Chert of the Panorama Formation in the Warrawoona Group of the Pilbara Craton, Australia [ de Vries , ; Westall et al ., ], consists of laminated black and white chert representing silicified volcanic sands and silts deposited in a mud flat/tidal channel environment [ de Vries et al ., ].…”
Section: Petrography Of Samplesmentioning
confidence: 99%
“…Here the two ISAR samples belonging to the “blind test” experiment [ Bost et al ., ] were analyzed by means of both a Fieldspec spectrometer and the SPectral Imager (SPIM) for testing the SPIM ability to identify mineral end‐members in rock slabs and mixtures. The SPIM is a visible and infrared imaging spectrometer that is a spare of the one on board the Dawn spacecraft [ De Sanctis et al ., ; Coradini et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy has been already employed in the identification of organic matter in meteorites [20]. Besides, it will be used onboard ExoMars2020 and Mars2020 missions, in order to identify organic compounds as indication of life in the extraterrestrial environment of Mars [21]. Therefore, despite no works about using Raman spectroscopy to detect organic compounds in LDGs and DGs were found in literature, we thought that this technique would be appropriate because of its experience in the study of terrestrial and extraterrestrial materials.…”
Section: Introductionmentioning
confidence: 99%